Impact of Cognitive Skills Training on Reducing Depression Among Clients During Pregnancy & Postpartum Referring to Health Centers - Nasrin Mousavinejad; Farkhondeh Amin shokravi; shohreh Shahmohammadi (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: Depression during pregnancy and after childbirth endangers mental health of the mother and physical health of the baby. Cognitive skills training can reduce the depression and anxiety of these periods. Thus, this study was designed to investigate the impact of cognitive skills training intervention program on women during pregnancy and postpartum referred to health centers in Khorramabad. Methods: This semi-experimental study was conducted on 120 pregnant women referred to the Health Centers. The participants were selected applying simple selection method. Data was gathered using Beck questionnaire before and two months after the educational intervention. Case group received the intervention program through lecturing. Data was analyzed applying SPSS16 and statistical tests (chi-square, t-test and regression) were applied. Results: Participants mean age was 27.29±5.76. The age range was between 18 and 39. After intervention, depression mean score changed from 38.13±7.45 to 29.95±5.12 the reduction in the case group statistically was significant (p=0.001). Conclusion: Training cognitive skills have a positive impact on reducing depression among pregnant women during and after pregnancy. Therefore, it is recommended that this intervention, after being valified by a few other researches, be combined in pre and postnatal care in health centers. Paper Type: Research Article.